Synthesis and characterisation of alites from reduced basic oxygen furnace slags. (September 2021) - Schraut, Katharina; Adamczyk, Burkart; Adam, Christian; Stephan, Dietmar; Meng, Birgit; Simon, Sebastian; von Werder, Julia
Abstract: Basic oxygen furnace slags (BOFS) are by-products of the steelmaking process. Several researchers have studied the production of Portland cement clinker and metallic iron from BOFS via a reductive treatment. In this study, we applied a carbothermal reduction of BOFS in a technical-scale electric arc furnace and characterised the clinker-like products. Those clinker-like non-metallic products (NMPs) had a chemical and mineralogical composition comparable to clinker for ordinary Portland cement (OPC) and contained large elongated alite crystals as major component. The pure NMPs reacted more slowly and achieved a lower degree of hydration compared with commercial OPC. If the reactivity of the products can be further increased by employing specific adaptations, it can be used as a full clinker substitute for OPC. Nevertheless, it is also an option to use the material without further modifications as a cement component or concrete addition, which contributes to the strength development in both cases.